Appearance and pathogenicity of ovarian parasite Marteilioides chungmuensis in the farmed Pacific oysters, Crassostrea gigas, in Korea - Park, MS; Kang, CK; Choi, DL; Jee, BY (NATL SHELLFISHERIES ASSOC, 2003)
The ovarian parasite Marteilioides chungmuensis that infects the ovaries of Pacific oyster Crassostrea gigas has increased in frequency in farmed oysters on the southern coast of Korean peninsula since the early 1990s. The appearance and pathogenicity of the ovarian parasite in the farmed oyster in Jinhae Bay, Korea, were investigated in 1996 and 1997. Infection by M. chungmuensis was highest during spawning (from June to August) and gonadal regenerating season of the oysters (from September to October), with prevalences ranging from 13.3 to 57.1% in 1996 and from 28.6 to 61.5% in 1997, respectively. The surveyed oysters showed signs of recovery from the infection after October. Glycogen levels were considerably lower in M. chungmuensis-infected oysters those that of uninfected oysters. A rapid accumulation of glycogen was observed in uninfected oysters together with the gonadal regeneration after the summer spawning. By contrast, no increase in glycogen content was found in infected oysters until the end of the investigation. Lipid levels were slightly higher in the infected oysters than in the uninfected oysters. Serum protein concentrations were significantly lower in the infected oysters than in the uninfected oysters. Also, the increase of serum protein concentration after the summer spawning was apparent in the uninfected oysters but not in the infected oysters. These results indicate that the infections by M. chungmuensis may have an adverse impact on metabolic recovery after spawning of the oysters. open 1 1 12 scie scopus